Experiências de trabalhadores/as pobres em Feira de Santana (1890-1930) - Silva, Mayara Pláscido (2012)
Based on the evidence contained in the criminal proceedings of the Feira de Santana District, regarding the crimes of Personal Injury and Homicide, which occurred between the 1890s and 1930s, we analyzed the experiences of poor men and women workers in the municipality, highlighting their customary practices, in the context of implementing measures for urban reordering and changing social behaviors, in the process of building a fair “civility”, based on denouncing experiences related to rurality, through local journalistic journals. Based on the experiences of workers in Feira de Santana, we sought to problematize the limits of the “civility” of the state, emphasizing their customary practices as indicative of the importance that these subjects had in that context of valuing commercial exchanges that occurred in the city. We emphasize the experiences of workers in the urban and rural areas of the municipality, residents of the alleys / sleepers, of the suburbs / suburbs of the city, as well as of workers who lived in the districts of Feira de Santana, highlighting how the movement of these subjects had impressed the city , characteristics related to delay and incivility.